2018
DOI: 10.18203/2320-6012.ijrms20183659
|View full text |Cite
|
Sign up to set email alerts
|

ANA immunofluorescence versus profile-how well they perform in autoimmune diseases: an analysis of their clinical utility in a tertiary care centre

Abstract: Background: While Immunofluorescence assay remains the gold standard for the detection of ANA, Immunoprofile by ELISA is being increasingly utilized in view of easy availability and quick results. The study was done to find out whether ANA profile results are comparable with IFA.Methods: About 100 patients who had undergone both immunofluorescence and Immunoprofile were included. Immunofluorescence correlation with profile and their correlation with the disease were analyzed; sensitivity, specificity and predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
1
4
1
Order By: Relevance
“…In contrast, the specificity of the two tests was different, whereas ELISA was more specific than IFA. This observation was also previously reported using different ELISA and IFA kits [ 18 - 21 ]. These variables were reflected in the positive and negative predictive values of the two procedures, where IFA showed a higher negative predictive value but a lower positive predictive value for SLE compared to ELISA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the specificity of the two tests was different, whereas ELISA was more specific than IFA. This observation was also previously reported using different ELISA and IFA kits [ 18 - 21 ]. These variables were reflected in the positive and negative predictive values of the two procedures, where IFA showed a higher negative predictive value but a lower positive predictive value for SLE compared to ELISA.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the sensitivity of IFA and ELISA were similar (77.78%). Previous studies showed that the sensitivity of the two tests was close to each other [18][19][20][21]. In contrast, the specificity of the two tests was different, whereas ELISA was more specific than IFA.…”
Section: Discussionmentioning
confidence: 89%
“…All the study participants and ANA-IIF-positive patients had a 4% negative ANA profile EIA, which is significantly lower than the 27% found by Petchiappan et al [15]. This difference may be attributed to the fact that our study detected more antibodies that were missed by the ANA profile EIA kits used in Petchiappan et al Doing an ANA profile EIA directly may save time, but if the specific antigen is not included in the kit, it may not detect the antibodies.…”
Section: Discussioncontrasting
confidence: 66%
“…A study by Tarazi et al reported a negative ANA test in a diagnosed patient with cutaneous lupus Erythematosus [ 14 ]. Also, Petchiappan et al reported that 9 of 10 negative ANA-IIF SLE were positive for autoantibodies detected by ELISA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Pachaiyappan V et al in South India also found that the most common pattern was nucleus speckled. 6 Where as, studies by Jacinth Angel etal. and Sebastian W et al in South India showed that nuclear homogenous pattern was the common pattern.…”
Section: Discussionmentioning
confidence: 98%